PENGUATAN TATA KELOLA KOPERASI DESA MERAH PUTIH MELALUI PENDAMPINGAN MANAJEMEN KELEMBAGAAN, KEUANGAN, DAN USAHA PRODUKTIF - Faisal Umardani Hasibuan; Maryam Jamilah; Aswadi Lubis; Muhammad Isa (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2026)
Strengthening cooperative governance is a crucial factor in enhancing the effectiveness, transparency, and sustainability of members’ businesses. This community service aims to improve institutional management, financial administration, and productive business development at the Merah Putih Village Cooperative, Tapanuli Selatan Regency. The method employed was intensive participatory assistance, including training in cooperative administration, financial record-keeping, business planning, and periodic performance evaluation. Data were collected through observation, in-depth interviews with cooperative management and members, and analysis of financial reports and business documents. The results indicate an improvement in the management’s capacity to prepare accurate financial statements, systematically manage member administration, and design productive business plans based on local needs. Furthermore, the program encouraged members to actively participate in decision-making and cooperative performance evaluation. Observed impacts include more organized administration, enhanced transparency in financial reporting, and better-implemented productive business initiatives that are targeted and sustainable. These findings demonstrate that systematic and continuous assistance can significantly improve the overall governance of village cooperatives, strengthen member participation, and ensure the sustainability of cooperative enterprises. The conclusion emphasizes that this model of institutional, financial, and productive business management assistance is feasible for replication in other village cooperatives with similar contexts.